Synthesis, Spectral Characterization, and Biological Evaluation of Transition Metal Complexes of Bidentate N, O Donor Schiff Bases - Sajjad Hussain Sumrra; Muhammad Ibrahim; Sabahat Ambreen; Muhammad Imran; Muhammad Danish; Fouzia Sultana Rehmani (Bioinorganic Chemistry and Applications)
New series of three bidentate N, O donor type Schiff bases (L1)–(L3) were prepared by using ethylene-1,2-diamine with 5-methyl furfural, 2-anisaldehyde, and 2-hydroxybenzaldehyde in an equimolar ratio. These ligands were further complexed with Co(II), Cu(II), Ni(II), and Zn(II) metals to produce their new metal complexes having an octahedral geometry. These compounds were characterized on the basis of their physical, spectral, and analytical data. Elemental analysis and spectral data of the uncomplexed ligands and their metal(II) complexes were found to be in good agreement with their structures, indicating high purity of all the compounds. All ligands and their metal complexes were screened for antimicrobial activity. The results of antimicrobial activity indicated that metal complexes have significantly higher activity than corresponding ligands. This higher activity might be due to chelation process which reduces the polarity of metal ion by coordinating with ligands.